2013
DOI: 10.5772/56806
|View full text |Cite
|
Sign up to set email alerts
|

Compliant Leg Architectures and a Linear Control Strategy for the Stable Running of Planar Biped Robots

Abstract: This paper investigates two fundamental structures for biped robots and a control strategy to achieve stable biped running. The first biped structure contains straight legs with telescopic springs, and the second one contains knees with compliant elements in parallel with the motors. With both configurations we can use a standard linear discrete-time state-feedback control strategy to achieve an active periodic stable biped running gait, using the Poincare map of one complete step to produce the discrete-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To design a finite-time controller, a desired trajectory is needed for the generalized coordinates. It has been shown that, for any arbitrary forward speed, the considered biped model has passive periodic running gaits which are unstable [4]. These gaits can be stabilized using some linear event-based controllers [4].…”
Section: Control Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…To design a finite-time controller, a desired trajectory is needed for the generalized coordinates. It has been shown that, for any arbitrary forward speed, the considered biped model has passive periodic running gaits which are unstable [4]. These gaits can be stabilized using some linear event-based controllers [4].…”
Section: Control Algorithmmentioning
confidence: 99%
“…It has been shown that, for any arbitrary forward speed, the considered biped model has passive periodic running gaits which are unstable [4]. These gaits can be stabilized using some linear event-based controllers [4]. In this research, we synthetize a finite-time controller to generate stable running gaits around the passive gaits.…”
Section: Control Algorithmmentioning
confidence: 99%
See 3 more Smart Citations